Adenosine in the Thymus - Köröskényi, Krisztina; Joós, Gergely; Szondy, Zsuzsa (Frontiers in Pharmacology, 2017)
Adenosine is an ancient extracellular signaling molecule that regulates various biological functions via activating four G-protein-coupled receptors, A1, A2A, A2B, and A3 adenosine receptors. As such, several studies have highlighted a role for adenosine signaling in affecting the T cell development in the thymus. Recent studies indicate that adenosine is produced in the context of apoptotic thymocyte clearance. This review critically discusses the involvement of adenosine and its receptors in the complex interplay that exists between the developing thymocytes and the thymic macrophages which engulf the apoptotic cells. This crosstalk contributes to the effective and immunologically silent removal of apoptotic thymocytes, as well as affects the TCR-driven T-cell selection processes.